BANKS’ SUSTAINABILITY AND FINANCIAL PERFORMANCE: THE ROLE OF CREDIT RISK - Soumaya Maztoul (Фінансово-кредитна діяльність: проблеми теорії та практики)
Under growing pressure to address sustainability imperatives, banks are progressively aligning their strategies with stakeholders' expectations. Gaining insights into how these initiatives impact banks' credit risk and financial performance is pivotal to ensuring economic stability and growth. In this context, the present article examines the effect of banks' sustainability on financial performance through its role in lessening credit risk. The study is based on a data set of 131 OECD commercial banks for 10 years. Using a recursive model, we test the mediating effect of non-performing loans in the relation between financial and ESG performances. We confirm our results using the Structural Equation Model that highlights the indirect effect. Empirical results show strong evidence that banks' financial performance is negatively related to non-performing loans and that banks with higher ESG scores have lower nonperforming loan ratios. Our study concludes that improving sustainability increases banks' financial performance by reducing credit risk. Integrating sustainability into banking operations enhances risk management which improves financial performance. Further results indicate that Social and Governance levels strongly contribute to this effect whereas the Environmental level has an ambiguous role. These results suggest that there is a need for banks to enhance ESG performance because of its beneficial effect on loan quality and financial performance. Findings have significant implications for bankers to manage their credit risk, for investors to understand the importance of sustainability and for regulators to enhance assessing ESG standards.